2017
DOI: 10.5897/jabsd2016.0279
|View full text |Cite
|
Sign up to set email alerts
|

Aging effect of two decade old technologies of bean stem maggot (Ophiomyia spp.) management options in Ethiopia: Baseline information generation for future research direction

Abstract: Haricot beans are the most important food and cash crop for most of the Ethiopian farmers. However, bean stem maggot (BSM) (Ophiomyia species) is limiting the production of the crop particularly in dry areas. Three species are involved in the infestation: Ophiomyia phaseoli, Ophiomyia spencerlla and Ophiomyia centrosematis. Two decades ago, two management options of BSM were developed and used for the last twenty years. However, there is a tendency of decline in effectiveness. Hence, the current experiment was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…However, after a decade and a half, these two varieties were tested for their reaction to BSM in BSM hot spot areas. The results obtained proved that Melkae became susceptible to BSM, while Beshebshe remained resistant to BSM (Mulatwa et al, 2017).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…However, after a decade and a half, these two varieties were tested for their reaction to BSM in BSM hot spot areas. The results obtained proved that Melkae became susceptible to BSM, while Beshebshe remained resistant to BSM (Mulatwa et al, 2017).…”
Section: Discussionmentioning
confidence: 80%
“…Various control methods have been recommended for the management of BSM, including the use of resistant varieties such as 'Beshbesh' and 'Melkae' (Tsedeke, 1990), intercropping, foliar insecticide application (Byabagambi et al, 1999), the use of deep straw mulching (Letourneau, 1994), and seed dressing (Byabagambi and Kyamanywa, 1997). Currently, the bean variety 'Melkae', which was previously reported as resistant, is becoming less resistant to BSM (Mulatwa, 2017). Moreover, new materials, both market types, and BSM-resistant varieties are being introduced from CIAT regularly.…”
Section: Introductionmentioning
confidence: 99%
“…Among BSM species, O. phaseoli and O. centrosematis are more prevalent in warmer areas, mostly in the south and south western part of the country at the elevation of <1800 m above sea level in Ethiopia (Mulatwa et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the inclination of the year after year production of common bean in Ethiopia asked for a BSM control strategy mainly towards the use of insecticides either as a seed treatment or foliar application since cultural approaches could merely control BSM to a limited extent. In the country, Mulatwa et al (2017) reported that the dominant seed dressing insecticide available for the last 228 Getachew Gudero Mengesha et al /Arch. Agric.…”
Section: Introductionmentioning
confidence: 99%